Islamic Guidance for Rape Victims in Mentally Retarded Individuals - Mierrina, Mierrina; Erika W, Nadia; Febriyanti, Rofida; Tri A, Riza; Egalita S.S., Tasya (Proceedings of International Conference on Da'wa and Communication, 2022)
The act of rape is a form of violence against women which is an example of the vulnerability of women's positions to men's sexual interests. Victims are forced to face misery, shame, and even trauma. The act of rape is very worrying because it will affect the psychological development of children, it can even cause lifelong trauma so that it affects their future. In this study, we will discuss how assistance using Islamic guidance is used to overcome trauma to victims of rape of individu with special needs. The selection of subjects here is based on the consent of the victims, psychologists, and victims. The results of interviews and observations show that Islamic guidance can be used to deal with trauma to rape victims, and requires a short time and intensive counseling process with victims.